Some characteristics of foreshocks and aftershocks of the 2022 ML6.8 Chihshang, Taiwan, earthquake sequence - Chen, Kou-Cheng; Huang, Bor-Shouh; Kim, Kwang-Hee; Wang, Jeen-Hwa (Frontiers in Earth Science, 2024)
Foreshocks and aftershocks occurred before and after the ML6.8 (Mw7.0) earthquake in eastern Taiwan on September 18, 2022. We explore the epicentral distribution and temporal variations for the mainshock, foreshocks, and aftershocks. Most of the events were located in the area around the Longitudinal Valley. Most foreshocks occurred around the mainshock, while the aftershocks happened outwards from the foreshock area. The temporal variations in seismic-wave energy show that the largest foreshock and the mainshock were responsible for releasing most of the energy during the earthquake sequence. In addition, the b values of the Gutenberg-Richter frequency-magnitude law were 0.62 for foreshocks, 0.87 for aftershocks, and 0.71 for the whole seismic activity by using the least squares method and 0.52 for foreshocks, 0.84 for aftershocks, and 0.65 for the whole seismic activity by using the maximum likelihood method. The b values increase from foreshocks to aftershocks, suggesting the possibility that the fluid pressure of faults during foreshocks is higher than that of the faults during aftershocks due to the outward migration of water. The p-value of the Omori-Utsu law for the aftershock sequence was estimated to be 0.92 for all aftershocks in the study, 1.39 for the aftershocks occurred in the first 6 days, and 1.30 for the aftershocks occurred in the first 12 days. The foreshock sequence could not be described by the inverse Omori law.